2021
DOI: 10.1111/btp.12934
|View full text |Cite
|
Sign up to set email alerts
|

Dung beetle activity had no positive effect on nutrient concentration or performance of established rainforest seedlings

Abstract: Dung beetle activity causes many changes in the soil when they remove feces from the surface. In temperate grasslands and in greenhouse experiments, these changes have been found to positively affect established plants, but information about these effects under natural conditions in tropical forests is practically nonexistent. In a tropical rainforest (Los Tuxtlas, Mexico), we carried out field experiments with seedlings of six tree species (Brosimum alicastrum, Calophyllum brasiliense, Cymbopetalum baillonii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…; but see Urrea-Galeano,Andresen, Coates, Mora Ardila, Diaz Rojas, et al, 2019;Urrea-Galeano et al, 2021).…”
unclassified
“…; but see Urrea-Galeano,Andresen, Coates, Mora Ardila, Diaz Rojas, et al, 2019;Urrea-Galeano et al, 2021).…”
unclassified
“…These studies gave us the first data suggesting that dung beetle activity might change the soil environment in a way that favors nutrient uptake and survival of seedlings established in the tropical forest understory. To gather more evidence, a third study in a different Mexican rainforest assessed the effects of dung beetle activity for the seedlings of six plant species, measuring foliar nutrients, growth, and survival (Urrea-Galeano et al, 2021). However, contrary to the previous results, no positive effect of dung beetle activity was detected for any of the variables in any of the seedling species.…”
Section: Plant Performancementioning
confidence: 84%
“…Whether dung beetle activity, through soil fertilization and/or bioturbation, has positive effects on the performance of tropical forest plants remains an unanswered question. At this point, to guide future studies, we can only summarize some recommendations that have been previously voiced by us or others (Nichols et al, 2008;Griffiths et al, 2016;Santos-Heredia et al, 2016;Urrea-Galeano et al, 2021): (i) to avoid extrapolating into natural conditions of tropical forests, results obtained in other study systems and regions; (ii) to carry out field experiments in tropical forest that would allow us to distinguish the effects that dung beetle activity has through fertilization vs. bioturbation on plant performance; (iii) to empirically measure the changes that feces burial by beetles causes in the tropical forest soil (i.e., physical, chemical, and biological changes) to better understand the mechanisms driving plant responses; (iv) to measure other responses in plants, such as herbivory and pathogen attack, since these plant antagonists are known to prefer plants with higher nutrient content; (v) to replicate these studies in forests that vary in soil characteristics (e.g., soil fertility, soil compaction, texture), and with plant species that differ in their functional traits (e.g., seed reserves, shade tolerance). There is much work to be done here.…”
Section: Plant Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Studies with other mammals have shown increased nitrogen, phosphorus, potassium, sulfur, and carbon in latrines (McGregor & Brown, 2010), with important consequences to plant diversity and composition (Shrestha & Moe, 2015). However, while recurrent defecation offers input of nutrients to the soil, it does not necessarily mean that plants will directly benefit from the extra nutrients (Urrea-Galeano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%